Development and Validation of Framework for Revitalization of Construction Crafts Apprenticeship Programmes - Auta, M. A. (Journal of Research in Industrial Technology and Educational Studies, 2026)
The construction industry in Nigeria is facing issues related to shortage of skilled craftsmen due to the progressive decline of traditional apprenticeship programmes. Despite their historical effectiveness in producing competent craftsmen through workplace-based, master-apprentice learning, construction crafts apprenticeships have deteriorated over recent decades. This study addresses this challenge by developing and validating a framework for the revitalization of construction crafts apprenticeship programmes. The proposed framework adopts a multi-level, systems-oriented approach structured around four interdependent pillars: (1) Policy and Regulatory Foundation, (2) Institutional and Partnership Architecture, (3) Curriculum and Delivery System, and (4) Support and Inclusivity Mechanisms. A sequential exploratory mixed-methods design was employed, comprising systematic literature review, semi-structured interviews, thematic analysis, expert validation through a modified Delphi technique and stakeholder applicability workshops. High consensus was achieved among diverse experts and stakeholders, confirming the framework’s relevance, completeness, feasibility, and cultural appropriateness for the Nigerian milieu. The validated framework offers a robust and practically oriented blueprint for rebuilding sustainable, high-quality apprenticeship systems that preserve the strengths of traditional workplace engagement while incorporating structured quality assurance, inclusivity measures, and responsiveness to contemporary demands such as sustainable construction and digital competencies.